Genetic and phenotypic heterogeneity of type 2 diabetes across Russian ancestry groups - Markelova, Ekaterina E.; Kononenko, Irina V.; Zubritskiy, Anatoliy; Podshivalova, Elizaveta; Matrosova, Alina; Plaksina, Evgeniya; Mansour, Saleem; Ahtyamov, Pavel; Shagimardanova, Elena; Vagapova, Gulnar R.; Maksimova, Nadezhda; Sydykova, Liubov A.; et al. (Frontiers in Endocrinology, 2025)
IntroductionType 2 diabetes mellitus (T2D) is a highly polygenic disease involving multiple biological pathways. Genetic ancestry may influence the predominant mechanisms driving T2D. Understanding how genetic background shapes T2D risk is crucial for developing personalized prevention and treatment strategies.MethodsWe analyzed ancestry-specific differences in T2D mechanisms and assessed the prevalence of T2D-associated genetic clusters, reflecting biological mechanisms underlying T2D onset and progression, in individuals from three Russian ancestry groups: Chechens, Tatars, and Yakuts. Previously developed polygenic scores were applied to evaluate cluster prevalence and clinical risk factors across ancestry groups.ResultsCluster-specific polygenic scores varied significantly between populations. Yakuts exhibited higher scores for β-cell dysfunction, hyper-insulin secretion, and lipid metabolism alterations, whereas Chechens and Tatars had higher scores for obesity-related mechanisms.Discussion/ConclusionsThe predominant mechanisms underlying T2D differ across populations. These ancestry-specific differences should be considered in public health recommendations and personalized medicine approaches.